Determinants of Ca²⁺ release restitution: Insights from genetically altered animals and mathematical modeling - Cely Ortiz, Diana Catalina Alejandra (2020)
Each heartbeat is followed by a refractory period. Recovery from refractoriness is known as Ca²⁺ release restitution (CRR), and its alterations are potential triggers of Ca²⁺ arrhythmias. Although the control of CRR has been associated with SR Ca²⁺ load and RYR2 Ca²⁺ sensitivity, the relative role of some of the determinants of CRR remains largely undefined. An intriguing point, difficult to dissect and previously neglected, is the possible independent effect of SR Ca²⁺ content versus the velocity of SR Ca²⁺ refilling on CRR. To assess these interrogations, we used isolated myocytes with phospholamban (PLN) ablation (PLNKO), knock-in mice with pseudoconstitutive CaMKII phosphorylation of RYR2 S2814 (S2814D), S2814D crossed with PLNKO mice (SDKO), and a previously validated human cardiac myocyte model. Restitution of cytosolic Ca²⁺ (Fura-2 AM) and L-type calcium current (ICaL; patch-clamp) was evaluated with a two-pulse (S₁/S₂) protocol. CRR and ICaL restitution increased as a function of the (S₁-S₂) coupling interval, following an exponential curve. When SR Ca²⁺ load was increased by increasing extracellular [Ca²⁺] from 2.0 to 4.0 mM, CRR and ICaL restitution were enhanced, suggesting that ICaL restitution may contribute to the faster CRR observed at 4.0 mM [Ca²⁺]. In contrast, ICaL restitution did not differ among the different mouse models. For a given SR Ca²⁺ load, CRR was accelerated in S2814D myocytes versus WT, but not in PLNKO and SDKO myocytes versus WT and S2814D, respectively. The model mimics all experimental data. Moreover, when the PLN ablation-induced decrease in RYR2 expression was corrected, the model revealed that CRR was accelerated in PLNKO and SDKO versus WT and S2814D myocytes, consistent with the enhanced velocity of refilling, SR [Ca²⁺] recovery, and CRR. We speculate that refilling rate might enhance CRR independently of SR Ca²⁺ load.